The vascular endothelial growth factor family in adverse pregnancy outcomes - Andraweera, P H; Dekker, G A; Roberts, C T (Human reproduction update, 2012)
Pre-eclampsia, small-for-gestational-age infants, preterm birth and recurrent miscarriage complicate a significant number of pregnancies. The vascular endothelial growth factor (VEGF) family of angiogenic growth factors is implicated in the pathophysiology of these complications. We aimed to elucidate the role of these angiogenic factors in placentation and to evaluate the predictive value of their protein concentrations and genetic variations in pregnancy complications. We performed a systematic search of PubMed, and retrieved original articles. The search included a combination of terms such as VEGF-A, placental growth factor (PlGF), kinase insert domain receptor, fms-like-tyrosine-kinase receptor 1, soluble fms-like-tyrosine-kinase receptor 1, pre-eclampsia, small-for-gestational-age infants, preterm birth, recurrent miscarriage, placenta, prediction and polymorphisms. This review summarizes the current knowledge of the roles of the VEGF family in early placentation and of the abnormalities in maternal plasma and placental expression of angiogenic proteins in adverse pregnancy outcomes compared with normal pregnancy. PlGF and sFLT-1 in combination with other clinical and biochemical markers in late first or second trimester appear to predict early-onset pre-eclampsia with a high sensitivity and specificity. However, VEGF family proteins do not have sufficient power to accurately predict late-onset pre-eclampsia, small-for-gestational age pregnancies or preterm birth. Functional polymorphisms in these angiogenic genes are implicated in pregnancy complications, but their contribution appears to be minor. Although the VEGF family has important roles in normal and complicated pregnancy, the current predictive value of the VEGF family as biomarkers appears to be limited to early-onset pre-eclampsia.